Anisotropic structure affects thickness measurement of laser cladding coating with surface ultrasonic wave based on cross-correlation function. (May 2015) - Liu, B.; Dong, S.
Abstract : Thickness evaluation of laser cladding coating with surface ultrasonic wave method was introduced in this research. Two surface ultrasonic wave transducers with 5 MHz frequency, distance between which was constant, were employed as signal emitter and receiver. Based on cross-correlation theory, the difference in time of flight between surface ultrasonic signals corresponding to different coating thickness was calculated. The relationship between the difference in time of flight and coating thickness is obtained. The results show that coating thickness evaluation is affected by microstructure of laser cladding coating, and accuracy of coating thickness evaluation increases as step length increases until it attains one cycle. In addition, influence of waveform distortion caused by microstructure of laser cladding coating on coating thickness evaluation is discussed. At last, verification test is carried out and the error is in the allowance range.